Prevalence of eight putative periodontal pathogens in atherosclerotic plaque of coronary artery disease patients and comparing them with noncardiac subjects: A case-control study - Jaideep Mahendra; Little Mahendra; Aishwarya Nagarajan; Kurien Mathew (Wolters Kluwer Medknow Publications, 2015)
Background: The study was aimed to assess the prevalence of periodontal pathogens namely Tannerella forsythia (T.f), Campylobacter rectus (C.r), Eikenella corrodens (E.c), Porphyromonas gingivalis (P.g), Treponema denticola (T.d), Prevotella nigrescens (P.n) ,Aggregatibacter actinomycetemcomitans (A.a), P.g (fi mA gene) and Prevotella intermedia (P.i), in the subgingival and the atheromatous plaque of patients with coronary artery disease (CAD), and comparing them with the noncardiac subjects thereby indicating the role of periodontal pathogenic bacteria in the progression of atherosclerosis in south Indian population. Materials and Methods: 51 cardiac and non cardiac subjects within the age group of 40-80 years,who met the eligibility criteria, were selected and categorized as the experimental and control group respectively. Total number of teeth was recorded, and oral hygiene was evaluated using Plaque Index and Oral Hygiene Index (OHI). Periodontal pocket depth and clinical attachment level were also assessed as a part of periodontal examination. Subgingival plaque samples were collected with the help of with Gracey's curette in both the groups. In experimental group, biopsy was obtained from the atherosclerotic plaque during Coronary artery bypass grafting CABG procedure. Both, subgingival and the coronary atherosclerotic plaque samples were subjected to polymerase chain reaction (PCR) analysis for identification of the periodontal bacteria. Statistical Analysis: Mean, standard deviation and test of significance of quantitative variables such as periodontal parameters were compared between experimental group and control group. Kappa measures of agreement was done to analyze the relationship between the presence/absence of microorganisms in the subgingival and atherosclerotic plaque samples in the experimental group. Results: The mean Plaque Index, Gingival Index, Russel's Periodontal Index, OHI, clinical attachment level, Pocket Depth Index was statistically significant in both the groups. Association of T.f, E.c, C.r, P.g, P.g (fi mA), T.d, P.i, P.n was significantly associated. A.a was absent in the control group, whereas only one patient in the experimental group was positive for the bacteria. Kappa analysis showed the significant association of periodontal bacteria T.f, C.r, P.g, P.g (fi mA), P.i and P.n in subgingival plaque and atherosclerotic plaque of the same patients of the experimental group. Conclusion: It is concluded that CAD subjects had higher prevalence of periodontal pathogens in subgingival biofilms as compared to the non cardiac subjects. Further, the number of bacteria was significantly associated between the subgingival and atherosclerotic plaques of the cardiac patients in south Indian population.